Biscuits, the World Cup and Nobel Prizes: The Puzzling Documentation of Shin Bet Interrogations. (9th May 2022) - Ballas, Irit; Dagan, Netanel
Abstract: Records kept by security authorities documenting potentially violent encounters are generally characterized by technocratic language and parsimonious content, which is intended to project an image of objective and impartial state officials. A qualitative analysis of 688 records covering interrogations of suspects in terror activities by the Israeli Security Agency (Shin Bet) presents a very different picture. They consist of representations of (1) hospitality—caring for the well-being of the person under interrogation; (2) camaraderie—amicable conversations between interrogator and interrogee; and (3) moral conviction—impassioned political or moral debates regarding the Israeli–Palestinian conflict. The analysis shows how unconventional documentation techniques in security interrogations may be used to preserve legitimacy; bolster professional prestige and makes a sophisticated use of a sense of secrecy.